2016
DOI: 10.1124/mol.116.105015
|View full text |Cite
|
Sign up to set email alerts
|

Role of the Second Extracellular Loop of the Adenosine A1 Receptor on Allosteric Modulator Binding, Signaling, and Cooperativity

Abstract: Allosteric modulation of adenosine A1 receptors (A1ARs) offers a novel therapeutic approach for the treatment of numerous central and peripheral disorders; however, despite decades of research, there is a relative paucity of structural information regarding the A1AR allosteric site and mechanisms governing cooperativity with orthosteric ligands. We combined alanine-scanning mutagenesis of the A1AR second extracellular loop (ECL2) with radioligand binding and functional interaction assays to quantify effects on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

21
73
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 55 publications
(94 citation statements)
references
References 54 publications
21
73
0
Order By: Relevance
“…Our results from both flexible and rigid receptor docking demonstrate that A 1 R PAMs also bind in this extracellular vestibule utilizing important interactions with E172 and K173. In the new paper by Nguyen et al, residues E172 and K173 were experimentally verified to mediate PAM activity of PD‐81,723 and VCP171 for A 1 R in agreement with our models . In addition, W156A was found to not affect allosteric ligand affinity, but did, probe‐dependently, reduce cooperativity …”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Our results from both flexible and rigid receptor docking demonstrate that A 1 R PAMs also bind in this extracellular vestibule utilizing important interactions with E172 and K173. In the new paper by Nguyen et al, residues E172 and K173 were experimentally verified to mediate PAM activity of PD‐81,723 and VCP171 for A 1 R in agreement with our models . In addition, W156A was found to not affect allosteric ligand affinity, but did, probe‐dependently, reduce cooperativity …”
Section: Resultssupporting
confidence: 85%
“…While this manuscript was in review, a paper by Nguyen et al was published that investigated the effects of alanine‐scanning mutagenesis and radioligand binding assays to determine their influence on allosteric ligand affinity, cooperativity, and efficacy of PAMs PD‐81,723 and VCP171 on A 1 R . The authors hypothesized that the allosteric site is most likely located within a hydrogen bonding network within the extracellular vestibule . This binding site is analogous to the allosteric binding site observed in the activated M 2 R crystal structure in complex with iperoxo and PAM LY2119620.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…Both experimental and computational studies suggested that flexibility of the ECL2 was important for activation and allosteric modulation of the A1AR. 39,44,45 Therefore, highly flexibility of the ECL2 contributed to activation of the A1AR and receptor coupling to the G protein.…”
Section: Mechanism Of Specific Adenosine Receptor-g Protein Interactimentioning
confidence: 99%
“…The CHARMM36 parameter set (58) was used for the protein and POPC lipids. For agonist ADO and antagonist PSB36, the force field parameters were obtained from the CHARMM ParamChem web server (59,60). Initial energy minimization and thermalization of the A1AR system follow the same protocol as used in the previous GPCR simulations (61).…”
Section: Simulation Protocolmentioning
confidence: 99%